2021
DOI: 10.1007/s00520-021-06089-w
|View full text |Cite
|
Sign up to set email alerts
|

How did women with breast cancer experience the first wave of the COVID-19 pandemic? A qualitative study

Abstract: Objective The ongoing COVID-19 global pandemic is a stressful experience that is particularly likely to negatively affect cancer patients. The goal of this qualitative study was to explore how breast cancer patients experienced the first wave of the COVID-19 outbreak. Methods As part of a larger study, 23 women accepted to take part in an individual phone interview investigating the psychosocial consequences of the COVID-19 pandemic. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 25 publications
7
71
0
2
Order By: Relevance
“…Consistent with this finding, Hyland and Jim showed that cancer patients felt worried, afraid and disappointed due to COVID-19 ( Hyland and Jim, 2020 ). In a qualitative study with patients with breast cancer, Savard et al revealed that the patients had increased psychological distress and worries about contracting COVID-19 ( Savard et al, 2021 ). Hintermayer et al found that cancer patients were worried about inaccessibility of treatment, diagnostic tests and/or follow-up care ( Hintermayer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consistent with this finding, Hyland and Jim showed that cancer patients felt worried, afraid and disappointed due to COVID-19 ( Hyland and Jim, 2020 ). In a qualitative study with patients with breast cancer, Savard et al revealed that the patients had increased psychological distress and worries about contracting COVID-19 ( Savard et al, 2021 ). Hintermayer et al found that cancer patients were worried about inaccessibility of treatment, diagnostic tests and/or follow-up care ( Hintermayer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patients also noted that they could not take advantage of their free time because of prohibition of social gatherings and travels. Savard et al also found out that social isolation led to psychological distress during cancer treatment ( Savard et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations